TINJAUAN YURIDIS TERHADAP JAMINAN FIDUSIA YANG DILELANG TIDAK MELALUI BADAN LELANG NEGARA (STUDY PADA PT. KEMBANG 88 MULTIFINANCE) - EDIM TOTONTA BANGUN (PREMISE LAW JURNAL, 2016)
Along with the rise of the development, the demand for transportation facilities is significantly increasing. In order to accommodate the society’s demands, economical growth, and credit system development in Indonesian society nowadays, any forms of financial assurance are required, where people need to make a loan with any movable property as the collateral, yet it can still be used by the financing institutions. In financing the purchase by installment of any automobiles, the financing institutions require the collateral for the vehicle. In fact, the leasing companies frequently sell the collateral of the auction without going through the State Auction Office that has been stipulated in the Law on Fiduciary Collateral. This way obviously breaks the Law and if it taken seriously, it can certainly become a legal issue. This research then made three conclusions, namely: In completing the financing agreement on motor vehicle installment in case the debtor defaults, withdrawal was firstly made, then the company did the selling, after that auction was done. The obstacles in the execution toward fiduciary collateral which properties were not registered were made underhanded. Therefore, the institutions who are involved in the practice get the administrative sanction stipulated in the Regulation of Minister of Finance No. 130/PMK.010/2012 regarding Fiduciary Collateral Registration. Keywords : Fiduciary, State Auction Office, Defaults